Water and Society 2013
DOI: 10.2495/ws130031
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and analysis of morphologic and hydrologic properties for Luvuvhu River Catchment in Limpopo province, South Africa

Abstract: Physiographic and topographic changes in Luvuvhu River Catchment are negatively impacting on the catchment hydrology of the area. A study was carried out to extract and analyze the morphologic and hydrologic properties using GIS techniques. Digital Elevation Modeling hydro-processing procedures were used within an ArcGIS environment where Arc hydro tools were used to extract and show the spatial distribution of the properties. A hydrologically correct Digital Elevation Modeling (DEM) was generated and used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…This is attributed to the use of high-resolution DEMs for the delineation. The methods used by Kundu et al, 2013 and those for this study are similar with a distinct difference in the DEMs used. As a result, the map delineated for this study presents a more complex drainage system that will require classification through ground proofing to determine the characteristics of the delineated rivers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is attributed to the use of high-resolution DEMs for the delineation. The methods used by Kundu et al, 2013 and those for this study are similar with a distinct difference in the DEMs used. As a result, the map delineated for this study presents a more complex drainage system that will require classification through ground proofing to determine the characteristics of the delineated rivers.…”
Section: Resultsmentioning
confidence: 99%
“…The study of headwater streams depends heavily on the knowledge of the stream ordering and size of the catchment being studied. These studies must be informed initially by well-defined drainage systems using geoinformatics techniques (Kundu et al, 2013). Kundu et al (2013) carried out similar research within the LRC, and their results are displayed in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 showed the area under forest/woodland, while Figure 3 showed the area under arable land. The pre-change geo-topes of planted forests and farms showed clear corridors, sizes, shapes and connectivity (Kundu et al [15]). Analysis of the results in both Figures showed that the dominant land cover classes had changed tremendously by 1989, where mixed classes of forest/woodland, grassland and shrubland covered 60% while agriculture and built-up area covered 40%.…”
Section: Land Cover Changesmentioning
confidence: 99%